16. ASSOCIATED FACTORS OF KNOWLEDGE, ATTITUDE AND PRACTICE OF REPRODUCTIVE HEALTH ON STUDENTS IN TIEN HUNG HIGH SCHOOL, DONG HUNG, THAI BINH IN 2023 (Vietnam Journal of Community Medicine, 2023)
Background: Reproductive health of adolescents is a critical issue in Vietnam. Improving knowledge on this subject, attitude toward practicing safe intercourse can prevent reproductive health issues, such as HIV/AIDS, unwanted pregnancy, abortion… and enhance adolescent health in general. Objective: Explore the associated factors on knowledge, attitude and practice toward adolescent reproductive health of students in Tien Hung high school, Dong Hung ward, Thai Binh in 2023. Methods: A cross-sectional study was conducted. Data were collected from 306 students by selfadministered questionnaire. Epidata 3.1 was used for data import, and data analysis was conducted by SPSS 14.0. Results: Knowledge, attitude and practice toward reproductive health of students associated with: (1) Attendance at adolescent reproductive health education sessions; (2) Sharing information regarding adolescent reproductive health with relatives/friends; (3) Seeking help from health practitioners/ school. These factors are statistically significant (p
Keywords: Knowledge, attitudes, practices, adolescent reproductive health, associated factors.